2016
DOI: 10.1038/srep33184
|View full text |Cite
|
Sign up to set email alerts
|

Superconductor to Mott insulator transition in YBa2Cu3O7/LaCaMnO3 heterostructures

Abstract: The superconductor-to-insulator transition (SIT) induced by means such as external magnetic fields, disorder or spatial confinement is a vivid illustration of a quantum phase transition dramatically affecting the superconducting order parameter. In pursuit of a new realization of the SIT by interfacial charge transfer, we developed extremely thin superlattices composed of high Tc superconductor YBa2Cu3O7 (YBCO) and colossal magnetoresistance ferromagnet La0.67Ca0.33MnO3 (LCMO). By using linearly polarized reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
0
9
1
Order By: Relevance
“…The second effect that should be taken into account is the charge transfer through the CMR/HTS interface ranging in distance from a few tenths of nm to several nm [7,8,9]. Gray et al [7] found a loss of 0.67 electrons per CMR monolayer in their CMR/HTS superlattices, which leads to conversion of the CMR layer to a paramagnetic or antiferromagnetic insulator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second effect that should be taken into account is the charge transfer through the CMR/HTS interface ranging in distance from a few tenths of nm to several nm [7,8,9]. Gray et al [7] found a loss of 0.67 electrons per CMR monolayer in their CMR/HTS superlattices, which leads to conversion of the CMR layer to a paramagnetic or antiferromagnetic insulator.…”
Section: Resultsmentioning
confidence: 99%
“…Gray et al [7] found a loss of 0.67 electrons per CMR monolayer in their CMR/HTS superlattices, which leads to conversion of the CMR layer to a paramagnetic or antiferromagnetic insulator. On the other hand, the electrons transferred through the CMR/HTS interface dope the Cu and Ba atoms in the YBCO and transform the superconducting YBCO to a Mott insulator.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and single layer SRO (1,2,4,8,12,20 u.c.) and LNO (1,2,4,8,12,20 u.c.) reference samples were grown on STO (001) substrates by pulsed laser deposition.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The electronic structure at the perovskite-oxide interface between two transition metal oxides features complex interactions among the lattice, charge, spin, and orbital degrees of freedom and shows many emergent physical properties, including high-temperature superconductivity [1], magnetoresistance [2], exchange bias (EB) [3], and ferroelectricity [4]. With regard to these complex oxide structures, many of which are epitaxially compatible, the past decade has seen rapid growth in materials science at the atomic level with the creation of heterostructures with unique properties [5].…”
Section: Introductionmentioning
confidence: 99%